PERBANDINGAN KADAR HEMOGLOBIN IBU HAMIL MENGGUNAKAN ALAT HEMOCHROMA PLUS METODE POCT DENGAN ALAT HEMATOLOGI SEMI OTOMATIK: THE DIFFERENCE IN HEMOGLOBIN LEVELS IN PREGNANT WOMEN USING THE HEMOCHROMA PLUS POCT METHOD WITH A SEMI-AUTOMATIC HEMATOLOGY DEVICE - Malihah, Malihah; Sundari, Titik; Yusmiati, Siti Nur Husnul (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2025)
Anemia is a condition where hemoglobin levels, hematocrit and red blood cell counts decrease below normal values. This research aims to find out. A simple examination of hemoglobin levels using an HB Meter with a Hemachroma Plus Tool, the POCT method, has the advantage of only requiring a small amount of capillary blood sample. Research title